Mali Financial Sector Assessment Program : Agricultural Finance - World Bank Group (World Bank, Washington, DC, 2016)
The performance of the Malian economy is largely dependent on the performance of the agricultural sector. The overall good growth in the Malian economy over the last several years is attributed to the agricultural GDP growth. Since 1995, the economy grew at about 5 percent per year until 2010, but a global recession, the military coup and terrorist activity caused a noticeable slowdown in GDP to about 1.2 percent in 2011-2012. The economic growth has resumed at a slow pace since 2013 and is currently estimated around 4.5 percent for 2014-2015. Agricultural development in general and agricultural finance in particular is hampered by a lack of quality data on the sector. Although improving, reliable statistical information is still lacking in Mali. There are often inconsistencies in agricultural data presented in the various reports available in the country. Although data on the main food crops and cotton are readily available, quality information on the high potential value chains, like mango and meat and dairy value chains, is less frequently provided. The lack of quality agricultural statistics makes public planning and analysis difficult and deters private sector investment.